Inovasi Kurikulum dan Metode Pembelajaran di Era Society 5.0 - Akbar Yusgiantara (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The transformation of Islamic education in Indonesia in the Society 5.0 era is crucial to address the rapid development of technology. The current era is marked by the application of technologies such as the Internet of Things (IoT), big data, and artificial intelligence (AI) in various aspects of life, including education. However, there is still a lack of research on how Islamic values can be integrated with modern technology in the Islamic education curriculum. This article offers creative solutions to integrate Islamic values with technology through multidisciplinary approaches and technology-based learning methods such as gamification, adaptive learning, and blended learning. By adopting modern technology without compromising fundamental Islamic values, Islamic education in Indonesia can evolve and contribute to shaping a generation that is not only intellectually capable but also morally upright. This study is expected to provide a new perspective on building a more comprehensive and relevant Islamic education in the modern era.